Integrated Application of Thiourea and Biochar Improves Maize Growth, Antioxidant Activity and Reduces Cadmium Bioavailability in Cadmium-Contaminated Soil - Haider, Fasih Ullah; Virk, Ahmad Latif; Rehmani, Muhammad Ishaq Asif; Skalicky, Milan; Ata-ul-Karim, Syed Tahir; Ahmad, Naeem; Soufan, Walid; Brestic, Marian; Sabagh, Ayman E. L.; Liqun, Cai (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination of croplands jeopardizes sustainable crop production and human health. However, curtailing Cd transfer and mobility in the rhizosphere-plant system is challenging. Sole application of biochar (BC) and thiourea (TU) has been reported to restrain Cd toxicity and uptake in plants. However, the combined applications of BC and TU in mitigating the harmful effects of Cd on plants have not yet been thoroughly investigated. Therefore, this study attempts to explore the integrated impact of three maize stalk BC application rates [B0 (0% w/w), B1 (2.5% w/w), and B2 (5% w/w)] and three TU foliar application rates [T0 (0 mg L–1), T1 (600 mg L–1), and T2 (1,200 mg L–1)] in remediating the adverse effects of Cd on maize growth, development, and physiology. Results demonstrated that Cd concentration in soil inhibited plant growth by reducing leaf area, photosynthesis activity, and enhanced oxidative stress in maize. Nevertheless, BC and TU application in combination (B2T2) improved the fresh biomass, shoot height, leaf area, and photosynthesis rate of maize plants by 27, 42, 36, and 15%, respectively, compared with control (B0T0). Additionally, the oxidative stress values [malondialdehyde (MDA), hydrogen peroxide (H2O2), and electrolyte leakage (EL)] were minimized by 26, 20, and 21%, respectively, under B2T2 as compared with B0T0. Antioxidant enzyme activities [superoxide dismutase (SOD) and catalase (CAT)] were 81 and 58%, respectively, higher in B2T2 than in B0T0. Besides, the shoot and root Cd concentrations were decreased by 42 and 49%, respectively, under B2T2 compared with B0T0. The recent study showed that the integrated effects of BC and TU have significant potential to improve the growth of maize on Cd-contaminated soil by reducing Cd content in plant organs (shoots and roots).